The British Raj in India : An Historical Review - Burke, S. M.; Quraishi, Salim al-Din (Karachi Oxford University Press, 1995)
This scholarly study is different from earlier books on the Raj in that it is neither hero-oriented nor self justifying. The emphasis instead is on world events and developments inside the subcontinent which influenced the conduct of the leaders, and affected the course of events. It is the crucial transfer of power process resulting in the partition of Britain's Indian Empire into two independent states that is appraised. The authors have made good use of the massive documentation made available by the British Government since 1983, as well as the unique archives kept in the British Museum. These have enabled the authors to throw some new light on the partition process, in particular on the workings of the Radcliffe Boundary Awards Commission.
Include Epilogues, Bibliography and Index.
Keywords: a